"Hidden" sexually transmitted infections among women in primary care health services, Amazonas, Brazil. (October 2014) - Rocha, Danielle Albuquerque Pires; Filho, Roberto Alexandre Alves Barbosa; Mariño, Josiane Montanho; Santos, Cristina Maria Borborema dos
Summary: This study describes the prevalence of infection by Chlamydia trachomatis, Neisseria gonorrhoeae and Trichomonas vaginalis in a female population in Amazonas, Brazil. We collected cervical samples from 361 women examined at 10 primary care health services in the city of Coari, Amazonas, Brazil. The women were interviewed about socio-economic data, clinical history and sexual behaviour. Pelvic examinations were performed and cervical specimens were collected for detection of pathogens by PCR. The prevalence of infection was: 12.7% for Trichomonas vaginalis, 6.4% for Chlamydia trachomatis and 1.4% for Neisseria gonorrhoeae . There were no statistically significant associations between infections by any of the pathogens nor by any pathogen alone with any clinical variable, socio-demographic data or sexual behaviour. This study draws attention to the need for surveillance and possible need for screening for Chlamydia trachomatis, which often progresses asymptomatically. For the significant prevalence found, attention should also be given to asymptomatic infection by Trichomonas vaginalis, since this pathogen has recently been implicated as a risk factor for HIV infection.